CHALLENGES IN THE USE OF ACTIVE LEARNING STRATEGIES WITH STUDENTS IN A PUBLIC SCHOOL. - Urio, Ângela; Brum Haag, Fabiana; Zanettini, Angélica; da Silva Filho, Cláudio Claudino; Franscechi, Vanilla Eloá; Barros de Souza, Jeane (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2017)
Objective: to understand the development of "new" didactic-pedagogical strategies and their relation in the school routine. Method: a qualitative study supported by Paulo Freire's assumptions, with 21 students from a public school, aged 10-17 years. Data collection was performed through the Snow Ball strategy and the analysis was developed by Minayo's operational proposal, characterized by two moments: study fundamentals and empirical facts. Results: students use the internet as a complement to their education. Regarding health education, some understood the real feeling of health prevention and promotion, while others understood it as a punitive action. It was evidenced insufficient mastery of the teachers on the group and scarce approach in health; the active learning methodologies were perceived as playful. Conclusion: the use of technologies as an adjunct to the health theme in the school environment is not used by students adequately. The understanding of actions is ambiguous, being useful to some and irrelevant to others.